2009
DOI: 10.1038/jhh.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Indexation of left ventricular mass to body surface area and height to allometric power of 2.7: is the difference limited to obese hypertensives?

Abstract: Whether left ventricular mass (LVM) should be normalized to different indexes in relation to body size is still debated. We sought to evaluate the prevalence of left ventricular hypertrophy (LVH) defined by different indexation criteria in a cohort of hypertensive subjects categorized according to body mass index (BMI). A total of 2213 essential hypertensive subjects included in the Evaluation of Target Organ Damage in Hypertension (ETODH) were divided in three groups according to BMI thresholds (o25, 25-29.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 31 publications
3
56
0
3
Order By: Relevance
“…!51/47 g/m 2.7 vs. !125/110 g/m 2 ) in a cohort of 2213 treated hypertensive patients categorized into three groups according to BMI (<25, 25-29.9 and !30 kg/m 2 ). We found that a stepwise increase in LVH prevalence occurred from normal to overweight and obese hypertensive patients when LVM was normalized to height 2.7 , whereas this trend was much less evident when LVM was indexed to BSA [10]. It should be pointed out that no significant differences in the prevalence of LVH defined by either criteria were observed in the lean hypertensive group.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…!51/47 g/m 2.7 vs. !125/110 g/m 2 ) in a cohort of 2213 treated hypertensive patients categorized into three groups according to BMI (<25, 25-29.9 and !30 kg/m 2 ). We found that a stepwise increase in LVH prevalence occurred from normal to overweight and obese hypertensive patients when LVM was normalized to height 2.7 , whereas this trend was much less evident when LVM was indexed to BSA [10]. It should be pointed out that no significant differences in the prevalence of LVH defined by either criteria were observed in the lean hypertensive group.…”
Section: Discussionmentioning
confidence: 57%
“…This calculation, however, has major mathematical limitations, as the three-dimensional variable LVM is divided by the twodimensional variable BSA and a geometric relationship exists between the two variables [8]. LVM indexed to BSA has been documented to markedly underestimate LVH prevalence in obese individuals, a condition that is more precisely identified by LVM indexed to height to allometric power of 2.7 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This latter criterion has been shown to provide the highest LVH prevalence rates; findings from population-based studies [40,41] and hypertensive cohorts [42] have shown that left-ventricular mass normalized to height to allometric signals identifies a higher portion of patients with LVH, as compared to BSA. In a previous analysis of 2213 treated hypertensive patients, we found that LVH defined by leftventricular mass/h 2.7 was more prevalent than that defined by left-ventricular mass/BSA (46 versus 31%); the corresponding figures in obese individuals were 71 and 40%, respectively [43]. Notably, recent findings show that LVH defined by left-ventricular mass/height 1.7 is more sensitive than left-ventricular mass/BSA or left-ventricular mass/ heght 2.7 in identifying obesity-related LVH and is more consistently associated with cardiovascular events and all-cause death [44].…”
Section: Totalmentioning
confidence: 88%
“…First, ratiometric indexing to BSA that is usually performed, may not be always appropriate, for instance, for linear dimension, such as left ventricular end-diastolic diameter (LVEDD). Second, previous studies have already addressed issue of left ventricular mass (LVM) indexing [4][5][6][7][8][9], but appropriate scaling and normative values of LVEDD, left ventricular end-diastolic volume (LVEDV), and left atrial volume (LAV) are not as well established [10]. Third, although women and men have different body composition, in practice, we still use the same thresholds for definition of left heart enlargement.…”
Section: Introductionmentioning
confidence: 98%